Influence of Knowledge and Religiousness on Students' Interest in using Halal Cosmetics in Bima City (Study of Students of Muhammadiyah Bima University) - Ririn Dwi Aryanti; Rafiuddin Rafiuddin; Muhammad Rasyad Al Fajar (JURNAL PENDIDIKAN IPS, 2025)
The phenomenon of increasing public awareness of halal products, including cosmetics, encourages the importance of research on factors that influence students' interest in using halal cosmetics. In Bima City, especially among students at Muhammadiyah University of Bima, aspects of knowledge and religiosity are important variables that are thought to play a significant role in the decision to use halal cosmetic products. This study aims to analyze the extent to which knowledge about halal cosmetics and the level of religiosity influence students' interest in selecting and using these products. The research method used is quantitative with a survey approach and distribution of questionnaires to 98 student respondents. The results of the study indicate that: (1) knowledge about halal cosmetics significantly influences students' interest, especially related to understanding the ingredients used and halal certification from official institutions; (2) the level of religiosity also has a significant influence, where students with a high level of religiosity tend to be more careful and selective in choosing products that are in accordance with Islamic values; and (3) simultaneously, knowledge and religiosity make a significant contribution to increasing interest in using halal cosmetics. These findings recommend the importance of continuous education and promotion of halal products, especially through religious and academic approaches. This research is expected to be a reference for manufacturers, academics, and religious institutions in increasing awareness and use of halal cosmetics among the younger generation.